Spliced transcripts of human cytomegalovirus. - Rawlinson, W D (1993)
The availability of the human cytomegalovirus (HCMV) genomic sequence has resulted in more extensive knowledge of the overall coding capacity of the virus. Using polymerase chain reaction and rapid sequencing techniques, we have studied the splicing of mRNAs from a number of the predicted open reading frames (ORFs). Splicing was found between the UL122(IE2) ORF present within major immediate-early (MIE) region 2 and the downstream ORF (UL118) predicted to encode an incomplete glycoprotein. This locates the IE2 3' donor site and provides evidence of a link between the MIE region and downstream ORFs. The downstream UL119-UL118-UL115 ORFs also undergo differential splicing, further increasing the known complexity of this region of the genome. A detailed map of the differential splicing within the region encoding the MIE ORF is presented. Also described are several previously unidentified spliced ORFs found in the long repeats and long unique regions, including one encoding a transcript with a large (4-kb) intron. The results show that spliced transcripts are encoded from throughout the genome at immediate-early, early, and late times postinfection.